Sarahland eaudiobook - Cohen, Sam (2021)
"Queer, dirty, insightful, and so funny" (Andrea Lawlor), this coyly revolutionary debut story collection imagines new origins and futures for its cast of unforgettable protagonists—almost all of whom are named Sarah. NAMED A MOST ANTICIPATED BOOK OF 2021 BY THE MILLIONS * OPRAH MAGAZINE * ELECTRIC LITERATURE * REFINERY29 In Sarahland , Sam Cohen brilliantly and often hilariously explores the ways in which traditional stories have failed us, both demanding and thrillingly providing for its cast of Sarahs new origin stories, new ways to love the planet and those inhabiting it, and new possibilities for life itself. In one story, a Jewish college Sarah passively consents to a form-life in pursuit of an MRS degree and is swept into a culture of normalized sexual violence. Another reveals a version of Sarah finding pleasure—and a new set of problems—by playing dead for a wealthy necrophiliac. A Buffy-loving Sarah uses fan fiction to work through romantic obsession. As the collection progresses, Cohen explodes this search for self, insisting that we have more to resist and repair than our own personal narratives. Readers witness as the ever-evolving "Sarah" gets recast: as a bible-era trans woman, an aging lesbian literally growing roots, a being who transcends the earth as we know it. While Cohen presents a world that will clearly someday end, "Sarah" will continue. In each Sarah's refusal to adhere to a single narrative, she potentially builds a better home for us all, a place to live that demands no fixity of self, no plague of consumerism, no bodily compromise, a place called Sarahland .